2020
DOI: 10.1155/2020/5691468
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Acupuncture‐Moxibustion Therapy on Chemotherapy‐Induced Leukopenia: A Systematic Review and Meta‐Analysis

Abstract: Background. Acupuncture-moxibustion therapy (AMT), as an integral part of complementary and alternative medicine, has been used for centuries in treatment of numerous diseases. Nevertheless, there is no available supportive evidence on the efficacy and safety of acupuncture-moxibustion therapy in patients with chemotherapy-induced leukopenia (CIL). The purpose of this study is to evaluate the efficacy and safety of acupuncture-moxibustion therapy in treating chemotherapy-induced leukopenia. Methods. Relevant s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 14 publications
(10 reference statements)
0
5
0
Order By: Relevance
“…Although recent systematic studies have shown relatively good effectiveness for such treatments, limitations such as the unknown active substance, heterogeneity in the treatment protocol and demographic indicators, lack of blinding, and the low number of participants in these studies should be taken into account. [ 23 - 26 ]…”
Section: Discussionmentioning
confidence: 99%
“…Although recent systematic studies have shown relatively good effectiveness for such treatments, limitations such as the unknown active substance, heterogeneity in the treatment protocol and demographic indicators, lack of blinding, and the low number of participants in these studies should be taken into account. [ 23 - 26 ]…”
Section: Discussionmentioning
confidence: 99%
“…A previous study has shown that acupuncture treatment can improve the immune system function of patients by increasing the antibody level and white blood cell count and protecting the immune organs, among others [ 67 ]. In addition, studies have confirmed the significant therapeutic effect and safety of acupuncture treatment for chemotherapy-induced leukopenia [ 68 ]. Therefore, we believe that acupuncture treatment can improve the mitochondrial function and tumor metabolism status of cancer patients by improving the immune status and regulating metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…More high-quality clinical studies are required to confirm the clinical value of acupoint stimulation. To date, several systematic reviews and meta-analyses have indicated that the use of acupuncture in the management of CIPN ( 78 ), CINV ( 79 ), and chemotherapy-induced leukopenia ( 80 ) is safe and effective. However, there are few clinical studies on the effects of acupoint stimulation on chemotherapy-induced myelosuppression and immunosuppression nor on tumor growth.…”
Section: Discussionmentioning
confidence: 99%